2001
DOI: 10.1046/j.1471-4159.2001.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhemoglobin induces caspase‐mediated cell death in cerebral endothelial cells

Abstract: Damaged endothelium is one of the pathological changes of the cerebral vasospastic vessels following subarachnoid hemorrhage. Our recent study shows that oxyhemoglobin (OxyHb) induces apoptosis in vascular endothelial cells. Apoptosis generally requires the action of various classes of proteases, including a family of cysteine proteases, known collectively as the caspases. This study was undertaken to investigate the activation of caspases and the ef®cacy of caspase inhibitors, z-IETD-fmk and z-LEHD-fmk, for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…The execution of caspase-mediated apoptosis is thought to be the result of a cascade of events converging in the activation of the executioner caspases -3, -6, or -7, where caspase-3 has been identified as a major downstream execution caspase (15). In the present study, treatment with the apoptosisinducer STS evoked a large activation of caspase-3.…”
Section: Discussionsupporting
confidence: 47%
“…The execution of caspase-mediated apoptosis is thought to be the result of a cascade of events converging in the activation of the executioner caspases -3, -6, or -7, where caspase-3 has been identified as a major downstream execution caspase (15). In the present study, treatment with the apoptosisinducer STS evoked a large activation of caspase-3.…”
Section: Discussionsupporting
confidence: 47%
“…MMP-9-mediated disruption of cellmatrix interactions promotes neuronal death (Gu et al, 2002). Here, we showed that similar mechanisms may be involved, insofar as endogenous apoptotic machinery has been previously demonstrated to be present in endothelial cells (Aoudjit and Vuori, 2001;Lin and Maiese, 2001;Meguro et al, 2001;Xu et al, 2001). After hypoxia-reoxygenation, MMP-2 and MMP-9 were upregulated in human brain endothelial cells, and subsequent degradation of extracellular matrix fibronectin appeared to trigger a form of caspase-mediated cytotoxicity.…”
Section: Fig 4 Mmp-mediated Degradation Of Matrix Fibronectin (A)supporting
confidence: 56%
“…In cerebral endothelial cultures, oxidative stress can trigger caspase-mediated pathways of cellular demise. [7][8][9] Because oxidative stress plays a critical role in ischemia and reperfusion, it is likely that similar caspase-mediated pathways operate in the vascular compartment after stroke. Nevertheless, the signaling pathways that regulate caspase activity during cerebral endothelial cell death remain to be fully elucidated.…”
mentioning
confidence: 99%